2017
DOI: 10.3906/elk-1510-219
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic slot-based carrier scheduling scheme for downlink multimedia traffic over LTE advanced networks with carrier aggregation

Abstract: Abstract:Carrier aggregation (CA) in long-term evolution advanced (LTE-A) networks is a promising tool for providing bandwidth extension for high data rate communication. In CA, the efficient scheduling of carriers has imposed a new challenge in the design of delay-sensitive carrier scheduling for mobile multimedia applications. In this paper, a new dynamic slot-based carrier scheduling scheme has been proposed for efficient resource allocation to support the quality of service (QoS) of mobile traffic over CA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…(4) when determining the priority of each user on each RB, on each CC and at each time. Besides the extended versions of the M-LWDF, other studies that investigated the packet scheduling algorithms in the literature include [6][7][8][9][10][11][12][13][14]. Based on our study, it was observed that the majority of these conventional multi-user packet scheduling algorithms offer to meet the desired QoS of either for RT packets or NRT packets.…”
Section: Introductionmentioning
confidence: 76%
“…(4) when determining the priority of each user on each RB, on each CC and at each time. Besides the extended versions of the M-LWDF, other studies that investigated the packet scheduling algorithms in the literature include [6][7][8][9][10][11][12][13][14]. Based on our study, it was observed that the majority of these conventional multi-user packet scheduling algorithms offer to meet the desired QoS of either for RT packets or NRT packets.…”
Section: Introductionmentioning
confidence: 76%
“…Closed-form Expression [132] Column Generationbased Algorithm [85] Dynamic Programming [135], [206], [229], [239], [240] Fountain Code [125], [126], [201] Greedy Algorithm [86]- [89], [100], [106], [207], [216], [241]- [243] Non-linear Programming [136], [244], [245] Lift-and-Project [246] Miscellaneous Multi-channel Mode [86], [87], [105], [137], [145], [146], [242], [247]- [250] Carrier Aggregation [84], [ [78], [83], [84], [100], [103], [121], [134], [137], [200], [209], [247], [249], [257]- [259] fully cognitive, they need to be equipped with learning and reasoning capabilities. Us...…”
Section: B2)mentioning
confidence: 99%
“…Carrier components may be non-contiguous over the same spectrum band or non-contiguous on different spectrum bands in this mode. In [84], a dynamic time-slotted carrier scheduling scheme was studied with the aim of efficient resource management and to support the QoS of mobile multimedia traffic over a CA-based framework. In this scheme, time slots are allocated to each component carrier according to the queue status and based on the priority of the application, which was defined based on the delay requirements.…”
Section: B24) Miscellaneous Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analytic model for high availability analysis of user equipments (UEs) in heterogeneous cellular networks (HetNets) using the benefits of both CA with CoMP is analyzed in [22,23]. A carrier scheduling scheme to enhance QoS of mobile traffic using CA is studied in [24]. Synchronization requirements of new 5G technologies including CA and CoMP are analyzed in [25].…”
Section: Related Workmentioning
confidence: 99%